2009
DOI: 10.1542/peds.2008-2952f
|View full text |Cite
|
Sign up to set email alerts
|

Equipment Options for Cough Augmentation, Ventilation, and Noninvasive Interfaces in Neuromuscular Respiratory Management

Abstract: This is a summary of the presentation on equipment options for cough augmentation, ventilation, and noninvasive interfaces in neuromuscular respiratory management presented as part of the program on pulmonary management of pediatric patients with neuromuscular disorders at the 30th annual Carrell-Krusen Neuromuscular Symposium on February 20, 2008. Pediatrics 2009123:S226-S230 T HE WIDESPREAD USE of noninvasive ventilation (NIV) developed with the polio epidemics during the 1940s and 1950s when the iron lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 16 publications
0
14
0
2
Order By: Relevance
“…13 Trebbia et al 20 conducted a study which demonstrated that MIC contributes 44%, the expiratory reserve volume 13% and the MEP 2% in a PCF increase in patients with neuromuscular diseases. The importance of this low-cost and highly effective technique, as observed in our study, where the PCF with AS-MEE technique was higher compared with the MEE technique, is that it produces a significant increase in PCF of 52%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Trebbia et al 20 conducted a study which demonstrated that MIC contributes 44%, the expiratory reserve volume 13% and the MEP 2% in a PCF increase in patients with neuromuscular diseases. The importance of this low-cost and highly effective technique, as observed in our study, where the PCF with AS-MEE technique was higher compared with the MEE technique, is that it produces a significant increase in PCF of 52%.…”
Section: Discussionmentioning
confidence: 99%
“…Its greatest efficacy has been reported in patients with neuromuscular diseases, particularly in DMD and SCI. 13 AC has been described as an assisted standard cough whereby the caregiver provides compression posteriorly and in cephalic direction through the abdomen which mimics the normal direction the diaphragm moves during a cough with functioning abdominals. This is preceded by several deep breaths with the assistance of the caregiver as the patient attempts to cough forcibly.…”
Section: Introductionmentioning
confidence: 99%
“…La CIM es un indicador indirecto de distensibilidad pulmonar. La técnica clásica está descrita con una bolsa de reanimación manual, una válvula unidireccional, un corrugado entre 20 y 30 cm y en el caso que exista fuga de aire, una pinza nasal 31 . Su mayor eficacia, se ha reportado en pacientes con enfermedades neuromusculares y lesionados medulares 10,32 .…”
Section: C) Estancamiento De Aire O Air Stacking (As)unclassified
“…30,31 This population also appears to benefit from cough assist devices using positive pressure. 32 There are also a number of small observational and randomized trials of using nocturnal NIV, particularly in stable COPD patients with hypercarbia. 30 Nocturnal NIV in restrictive diseases appears to have a more consistently positive database, and it may help in airway clearance in cystic fibrosis.…”
Section: Mechanical Ventilatory Supportmentioning
confidence: 99%